Nanocrystalline Cellulose/Polyvinylpyrrolidone Fibrous Composites Prepared by Electrospinning and Thermal Crosslinking - Katrina M. Hatch; Jana Hlavatá; Katherine Paulett; Tatsiana Liavitskaya; Sergey Vyazovkin; Andrei V. Stanishevsky (International Journal of Polymer Science)
Nanocellulose/polyvinylpyrrolidone (nCel/PVP) fibrous composite materials containing rod-like nanocrystalline cellulose particles with the lengths varying in the range from 100 to 2000 nm were prepared by using DC electrospinning. The particle size had a strong effect on the precursor viscosity, process efficiency, and resulting fiber diameter. The thermal crosslinking of nCel/PVP composite nanofibers with up to 1.0 :  8.0 nCel/PVP weight ratio resulted in fibrous membranes with textural, air transport, and mass swelling properties varying significantly with the size of cellulose particles. The presence of nCel particles increased the oxidation resistance of PVP during the crosslinking and affected the morphological changes of nCel/PVP fibrous membranes in aqueous solutions. Particles with the smallest size improved the strength of the membrane but decreased its mass swelling capacity, whereas the larger particles led to a more porous and flexible, but mechanically weaker, membrane structure with a higher swelling ability. Thus, by using the nCel particles of different size and shape, the properties of nCel/PVP composite fibrous membranes can be tailored to a specific application.